Interaction between Ground Water and Surface Water in Porong River, Sidoarjo - Haromain, Safira Anisah; Yuliani, Emma; Andawayanti, Ussy; Imai, Tsuyoshi; Aliyah, Firda Samaniyatul (Fakultas Teknik, Universitas Brawijaya, 2024)
The Lapindo mud phenomenon has been going on for 17 years, causing damage to the land and subsurface geological structures which raises concerns about reducing groundwater quality. This research aims to determine groundwater flow patterns based on surface contours around the Porong River which were analyzed using Surfer 13 software, and understand the relationship between groundwater and surface water through physical properties with correlation coefficients using Rstudio, as well as to identify the chemical characteristics of surface water and groundwater using the Trilinear Piper Diagram. Based on the research results, the groundwater flow pattern moves from northeast to southwest, and there is interaction between the two as indicated by the physical properties of the water. The correlation coefficient value ranges from 0.615 to 0.997, meaning that the relationship between groundwater and surface water is moderate to strong. Both groundwater and surface water have the same chemical type, namely mostly containing alkaline earth and weak acids. In addition, this research reveals the exploration of the impact of heavy metal parameters, namely Copper (Cu), from the Lapindo mud in the Porong River and residents' dug wells. In conclusion, this research shows the interaction between groundwater and surface water in the Porong River.